Performance Of Pure Danish Holstein Friesian Bulls Under Indian Management And Tropical Climatic Conditions - Tiwari, Ritesh; Mishra, G. K.; Singh, R. B; Saxena , S. K.; Siddiqui , M. U. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Data on 1798 ejaculates obtained from three high pedigree pure Danish Holstein Friesian bulls were analyzed to observe the influence of Indian management and tropical climatic conditions on various seminal characteristics. The effect of seasons was significant (P<0.05) for ejaculate volume, sperm output per ejaculate, initial motility and post thaw motility, bull to bull variation was observed in all parameters except initial motility and post thaw motility. Sperm concentration was non significant between seasons. Ejaculate wise data analysis revealed that volume and initial motility for the first ejaculate did not differ significantly between bulls however rest of the parameters differed significantly between bulls, the effect of season was significant in all parameters except sperm concentration in both the ejaculates and post thaw motility for the first ejaculate.